2018
DOI: 10.3389/fphys.2018.01059
|View full text |Cite
|
Sign up to set email alerts
|

Strength-Endurance Training Reduces the Hamstrings Strength Decline Following Simulated Football Competition in Female Players

Abstract: Hamstring strains are the most common injury in multiple sprint sports, with inadequate eccentric hamstring strength and fatigue identified as important risk factors. Resistance training interventions aimed at reducing injury risk typically focus on the development of maximum strength, while little is known about the impact of training on hamstring fatigue resistance. The present study compared the effects of strength endurance (SE) with a strength intervention (S) on the eccentric hamstring strength decline i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 59 publications
0
18
0
1
Order By: Relevance
“…Previous studies applying ST in female football players have assessed strength outcomes in isometric [35] or isokinetic exercises [36, 37], making comparisons with the present study unattainable as we measured dynamic squat strength [38]. Elite male football players experienced a 52% increase in absolute 1RM following 16 sessions of MST over 8 weeks [23].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies applying ST in female football players have assessed strength outcomes in isometric [35] or isokinetic exercises [36, 37], making comparisons with the present study unattainable as we measured dynamic squat strength [38]. Elite male football players experienced a 52% increase in absolute 1RM following 16 sessions of MST over 8 weeks [23].…”
Section: Discussionmentioning
confidence: 98%
“…While, interactions between player fitness or neuromuscular characteristics and fatigue-recovery kinetics in the posterior chain test have not been reported, Delextrat et al [31] reported that increased hamstrings strength-endurance reduced the magnitude of acute eccentric hamstring fatigue following a simulated match, but it is not known if this characteristic would also mediate the magnitude of residual fatigue. Further investigation of the interaction between fatigue response to/recovery from competition, and aspects of hamstrings neuromuscular performance—including strength, rate of force development or strength-endurance, and other potential mediators such as fascicle length [32] is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…This greater susceptibility to fatigue in the hamstrings muscle group may mean that other physical qualities, such as repeated sprint ability, aerobic capacity, or posterior chain local strength-endurance, are more important in determining fatigue-recovery profile in this muscle group. This may also suggest that in players with the highest HSR and match demands, overall aerobic and buffering capacity [43,44] and metabolic adaptations in the relevant muscle fibres may not only confer greater fatigue resistance during competition [45] but may also influence residual neuromuscular deficit/enhance recovery.…”
Section: Discussionmentioning
confidence: 99%